Dual impact of ambient humidity on the virulence of Magnaporthe oryzae and basal resistance in rice. (10th October 2022) - Qiu, Jiehua; Liu, Zhiquan; Xie, Junhui; Lan, Bo; Shen, Zhenan; Shi, Huanbin; Lin, Fucheng; Shen, Xiangling; Kou, Yanjun
Abstract: Humidity is a critical environmental factor affecting the epidemic of plant diseases. However, it is still unclear how ambient humidity affects the occurrence of diseases in plants. In this study, we show that high ambient humidity enhanced blast development in rice plants under laboratory conditions. Furthermore, we found that high ambient humidity enhanced the virulence of Magnaporthe oryzae by promoting conidial germination and appressorium formation. In addition, the results of RNA‐sequencing analysis and the ethylene content assessment revealed that high ambient humidity suppressed the accumulation of ethylene and the activation of ethylene signaling pathway induced by M. oryzae in rice. Knock out of ethylene signaling genes OsEIL1 and OsEIN2 or exogenous application of 1‐methylcyclopropene (ethylene inhibitor) and ethephon (ethylene analogues) eliminated the difference of blast resistance between the 70% and 90% relative humidity conditions, suggesting that the activation of ethylene signaling contributes to humidity‐modulated basal resistance against M. oryzae in rice. In conclusion, our results demonstrated that high ambient humidity enhances the virulence of M. oryzae and compromises basal resistance by reducing the activation of ethylene biosynthesis and signaling in rice. Results from this study provide cues for novel strategies to control rice blast under global environmental changes. Summary statement: This study found that high ambient humidity enhanced blast development in rice plants by promoting conidial germination and appressorium formation of M. oryzae and suppressing the activation of ethylene signaling pathway induced by M. oryzae in rice.